Peran Industri Kecil Dalam Meningkatkan Penghasilan Pekerja Pada Industri Kecil Sepatu Sandal Wedoro Sidoarjo - Juliani Pudjowati (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2014)
Setra Smes in Sidoarjo has the potentialto bedeveloped and required bythe government toreduce unemployment, because the smes to absorb labor forcein large numbers. Such as smes slipper Wedoro hamletin the village of Sidoarjo Hemisphere. Smes also has arolein increasing the revenueof its workforce. The importance of incomegiven tolaborin order to increase employee discipline. The focus of this research is to explain how the role of home industry in increasinglabor income. In order to determinean and alyzethe role ofhome industryin increasing labor income at home industry slipper Wedoro village hamlet Hemisphere. This study uses a qualitative method with an observational case study approach. With this approach is expected to be captured empirical particulars and details of the actual research analysis unit, whether it concerns the lives of individuals and social unit within the community